Pengukuran Kinerja Keuangan PT Telkom Indonesia (Persero) Tbk Menggunakan Economic Value Added (EVA), Market Value Added (MVA), dan Financial Value Added (FVA) - Mulatsih; Arif Hartanto (INVESTASI : Inovasi Jurnal Ekonomi dan Akuntansi, 2026)
This study aims to analyze the financial performance of PT Telkom Indonesia (Persero) Tbk for the 2022–2024 period using the Economic Value Added (EVA), Market Value Added (MVA), and Financial Value Added (FVA) methods. The study employs a quantitative descriptive approach utilizing secondary data obtained from the company's annual financial reports. The results indicate that PT Telkom Indonesia (Persero) Tbk consistently generated positive EVA, MVA, and FVA values ??throughout the study period. A positive EVA value demonstrates the company's ability to generate operating profit exceeding the cost of capital employed. A positive MVA value reflects that the company's market value exceeds its book value of equity, indicating the creation of value for shareholders. Furthermore, a positive FVA value indicates the company's ability to generate financial value added after accounting for the cost of capital and economic depreciation. Despite fluctuations observed during the study period, the company demonstrated strong and stable overall financial performance, successfully creating economic and financial value for investors.